(3ehShYJj GdChdi eY hjfj GdOHOhH h CUObGFgs (3GdCQVs - (3EHQGgje, OGdjG eMeOs; (3fgVI eUQ ddfTQs (3EOGQI GdfTQ hGdJQLeIs ((3GdbGgQIs (3OGQ fgVI eUQs, 2024)
(3OhQGJ GdCQV hGdSMGH hGdCYGUjQ hJjGQGJ GdeGA (B. . (3eLQO CeKdI Ydi GdehVhYGJ GdJj fJYQa YdjgG aj gPg GdehShYI Yf chcHfG (B"(3GdCQV GdPj fYjT Ydjg(B. (3JMJhj gPg GdehShYI Ydi UhQ NdGHI SJdaJ GfJHGg GdCWaGd GdUZGQ HGdEVGaI deYdheGJ ePgdI SJhSY eOGQcge (B. . . (3SfZhU eYkG aj GdeSWMGJ GdeGFjI, hfSJcTa CSQGQ MjGI GdcGFfGJ GdHMQjI(B. (3ceG SfLhH GdUMGQj dfJYQa Ydi WQb JYGed eNJda GdcGFfGJ eY OQLGJ GdMQGQI TOjOI GdGQJaGY, Ke SfUYO Edi GdSeGA dfJYQa Ydi GdCSHGH GdYdejI dgHhH GdYhGUa hJZjQ GdaUhd(B. (3JRNQ gPg GdehShYI HGdeYdheGJ GdeeJYI GdJj SJLYd GdCWaGd jSJeJYhf hge jJYdehfs
(3Ydhe eHSWIs
Keywords: (3GdYdhes